2017
DOI: 10.9790/1813-0606025061
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Firm size and Diversification on Capital Structure and FirmValue (Study in Manufacturing Sector in Indonesia Stock Exchange)

Abstract: This study aims to examine and analyze whether firm size, diversification, and capital structure to the firm value. The design of this study was to raise the theory of Modigliani and Miller and fundamental theories in financial management that discuss some of the functional relationship fundamental variables that determine the capital structure and corporate value. The locations of this study are in the Stock Exchange Indonesia at Jalan Sudirman Jakarta and Makassar Capital Market Information Center. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 28 publications
0
9
0
9
Order By: Relevance
“…Ukuran perusahaan mampu memoderasi hubungan CSR dengan nilai perusahaan disebabkan karena perusahaan memberikan kesempatan untuk dapat berkembang dalam aspek yang perlu diperhatikan dalam kesejahteraan masyarakat yang tidak hanya untuk kepentingan perusahaan semata. Ukuran perusahaan ini didukung oleh pernyataan dari Pratama dan Wiksuana (2016); Meizari dan Oktaviani (2017); Andawasatya et al 2017; Hamyat,et al (2017); Sofia dan Akhmadi (2018).Ukuran perusahaan yang diperhitungkan dengan total aktiva dimiliki perusahaan ini meliputi besar kecilnya perusahaan yang sekaligus berimbas pada luasnya pengungkapan CSR yang diakibatkan oleh aktivitas perusahaan yang banyak inilah untuk dapat meningkatkan nilai perusahaan maka dibutuhkanlah CSR tersebut.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Ukuran perusahaan mampu memoderasi hubungan CSR dengan nilai perusahaan disebabkan karena perusahaan memberikan kesempatan untuk dapat berkembang dalam aspek yang perlu diperhatikan dalam kesejahteraan masyarakat yang tidak hanya untuk kepentingan perusahaan semata. Ukuran perusahaan ini didukung oleh pernyataan dari Pratama dan Wiksuana (2016); Meizari dan Oktaviani (2017); Andawasatya et al 2017; Hamyat,et al (2017); Sofia dan Akhmadi (2018).Ukuran perusahaan yang diperhitungkan dengan total aktiva dimiliki perusahaan ini meliputi besar kecilnya perusahaan yang sekaligus berimbas pada luasnya pengungkapan CSR yang diakibatkan oleh aktivitas perusahaan yang banyak inilah untuk dapat meningkatkan nilai perusahaan maka dibutuhkanlah CSR tersebut.…”
Section: Pendahuluanunclassified
“…Peningkatan ukuran perusahaan berdasarkan aset inilah yang menjadikan perusahaan farmasi mampu berkembang dan tumbuh dengan baik sehingga perlahan akan meningkatkan nilai perusahaan. Sehingga hipotesis 2 diterima dan sejalan dengan penelitian Pratama dan Wiksuana (2016); Meizari dan Oktaviani (2017);Andawasatya, et al (2017);Hamyat,et al,(2017); Sofia dan Akhmadi (2018).…”
Section: Pengaruh Ukuran Perusahaan Terhadap Nilai Perusahaanunclassified
“…These findings also are claimed by Kurshev and Strebulaev (2006) who found that there is a significant positive correlation between firm size and CS for the performance of the firm. The availability of funds and company profit as indicated by Hamyat et al (2017) is largely affected by the size of the company. A small business found it difficult to raise debt funds.…”
Section: Discussionmentioning
confidence: 99%
“…Based on simultaneous testing results, it is known that the Fcount value (19,336)> Ftable (3,295), so that Ho is rejected, meaning that Fcount is greater than Ftable, which means company Size and capitalsStructure have a significant effect on company value in food and beverage companies [11]. The test results are the same as the results of previous studies entitled "The effect of firm size, institutional ownership, managerial ownership, profitability, capital structure on the value of manufacturing companies listed in LQ 45 for the period 2012-2014" , mentions that company size and capital structure have a significant effect simultaneously on Company Value [12].…”
Section: Methodsmentioning
confidence: 99%
“…Capital Structure has been one of the most controversial issues in the theory of finance during past 40 years [2]. Furhermore, capital structure is in prportion to the number of short term debt that is permanent, long term debt, preference shares and ordinary shares [3].…”
Section: Introductionmentioning
confidence: 99%